PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR DAN RETENSI SISWA MATERI EKOSISTEM KELAS X - Ibnu Thalib; Kurnia Ningsih; Eko Sri Wahyuni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research was to find out the students’ achievement and retention of ecosystem learning material at class X MIA SMA Negeri 4 Pontianak. Pre-experimental design with one shot case study planning was chosen as the form of this research. Class X MIA 5 was taken as the sample in this research by deploying purposive sampling technique in determining the sample. The instrument administered in this research was multiple choice test consisted of 20 questions. On average, students’ learning result was 18, 16 by using scientific approach and the retention result was 17, 38. From normalized gain test using scientific approach, students’ learning result in ecosystem learning material was 0, 80 considered as high. Furthermore, students’ retention score in ecosystem learning material by using scientific approach was 95, 70% which categorized as high. Therefore, it can be concluded that teaching by using scientific approach gives positive impact on students’ learning achievement and retention at ecosystem learning material at class X MIA 5 SMA Negeri 4 Pontianak. Keywords: Ecosystem Learning Material, Learning Result, Retention,Scientific Approach